Perilaku mahasisawa pengguna vapor dan dampaknya pada kesehatan - Ovi Tri Ariyani; Mury Ririanty; Iken Nafikadini (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
ABSTRACT Vapor today has became a phenomenon among the public, especially students. This is in line with the finding of Jember University students who are members of the user community vapor 4 and 3 groups that selling tools and vapor liquid in social media, especially facebook. The factors of students using the vapor is following the development of lifestyle, steam vapor generated numerous and uniqe, has the flavors, and can eliminate the addiction to conventional cigarettes. This study aims to analyze the behavior of students who use vapor and its impact on health. The research method used is qualitative with the type of phenomenological research. This research was conducted on 4 students in University of Jember. The results of this study indicate that the behavior of vapor use by first informant is determined by lack of knowledge about the impact of vapor for health, a negative attitude that considers vapor safer than cigarettes, vapor as a tool to stop smoking, and personal references especially friends and youtuber in making decisions using vapor. With the result that, the main informants will continue to use vapor because of lack of knowledge, a negative attitudes, and strong of personal references.